Chemical mechanical polishing solutions comprising molecular sieve particles

By using molecular sieve particles as abrasives or catalysts in chemical mechanical polishing fluids, the problem of polishing rate and surface quality in existing technologies is difficult to balance, and high -efficiency and low -scratched carbon wafer polishing effects are achieved.

CN119350976APending Publication Date: 2025-01-24JIANGSU JICUI CATALYTIC MATERIALS CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411908525.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

During the polishing process of silicon carbide wafers, it is difficult to achieve a balance between high polishing rate and high surface quality, and the high hardness of the abrasive particles leads to the risk of scratches.

Method used

Use a chemical mechanical polishing solution containing molecular sieve particles, and use it in combination with oxidants and additives to utilize the acidity/alkalinity, high specific surface area and rich pore structure of the molecular sieve as abrasive particles or catalysts to promote the chemical mechanical polishing reaction.

Benefits of technology

The removal rate of a variety of wafer materials has been significantly increased, the flatness of the high surface is ensured, the hardness of the abrasive particles is reduced, the risk of scratching is avoided, and the price of molecular sieve materials is low, environmentally friendly, and suitable for industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350976A_ABST
    Figure CN119350976A_ABST
Patent Text Reader

Abstract

The invention discloses a chemical mechanical polishing solution containing molecular sieve particles, which is prepared by the following steps: S1, mixing the molecular sieve particles with deionized water to obtain a solution A; s2, dissolving an oxidizing agent in deionized water to obtain a solution B; and S3, mixing the liquid A with the liquid B, adding an auxiliary agent, and uniformly stirring to obtain the polishing solution. The chemical action in chemical mechanical polishing is promoted by utilizing the properties of acidity / alkalinity, high specific surface area, rich pore structure, ion exchange performance, doping of molecular sieve framework elements and the like of the molecular sieve, and the removal rate of various wafer materials can be greatly improved. The molecular sieve has strong acidity and can obviously improve the oxidation rate of various wafer materials, so that the removal rate is improved; the molecular sieve has a high specific surface area and a rich pore structure, and the high specific surface area can provide more active sites, so that the adsorption of reactants is facilitated; the abundant pore structure is beneficial to mass transfer and diffusion of reactants, and mass transfer bottlenecks are reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of chemical mechanical polishing, and in particular to a chemical mechanical polishing liquid containing molecular sieve particles. Background Art

[0002] Chemical-Mechanical Polishing (CMP), also known as Chemical-Mechanical Planarization, is a means of achieving global flatness in integrated circuit manufacturing. It is used to flatten wafer materials (such as single crystal silicon wafers, silicon carbide wafers, sapphire, gallium nitride, gallium arsenide and other wafer materials) to obtain a surface that is both flat and free of scratches and impurities to meet the needs of subsequent semiconductor processes.

[0003] The basic principle of chemical mechanical polishing is to rotate the workpiece to be polished relative to the polishing pad under a certain downward pressure and in the presence of a polishing liquid (a mixture of ultrafine abrasives, chemical reagents and liquid media), and use the mechanical grinding of the abrasives and the corrosion of the chemical reagents to complete the material removal on the workpiece surface and obtain a smooth surface. CMP is a technology that combines chemical and mechanical actions. Its process is quite complicated and has many influencing factors. First, the workpiece surface material reacts chemically with the chemical reagents, catalysts, etc. in the polishing liquid to form a relatively easy-to-remove soft layer. Then, the soft layer is removed under the mechanical action of the abrasives in the polishing liquid and the polishing pad, so that the workpiece surface is exposed again, and then a chemical reaction is carried out. In this way, the workpiece surface is polished in the alternating chemical and mechanical processes. Commonly used abrasives include silica sol, alumina (various crystalline forms of alumina, such as α-alumina, γ-alumina, etc.), cerium dioxide, zirconium dioxide, diamond, silicon carbide, etc. Abrasives mainly provide mechanical scraping, and their hardness, particle size, distribution, morphology, etc. have a great influence on the removal rate and surface quality. Commonly used chemical reagents include acids, alkalis, oxidants, etc. For example, hydrogen ions under acidic conditions corrode single crystal silicon and various metal materials; hydroxide ions under alkaline conditions corrode sapphire, single crystal silicon, silicon dioxide and other materials; oxidants such as potassium permanganate and hydrogen peroxide have oxidative corrosion effects on various wafer materials, such as silicon carbide, gallium nitride, gallium arsenide, various metal materials, etc. It is worth pointing out that the oxidizing property of the oxidant is affected by the pH value of the solution, and the oxidizing property is usually stronger under acidic conditions.

[0004] As the third-generation wide bandgap semiconductor material, silicon carbide has the properties of high frequency, high efficiency, high voltage resistance, high temperature resistance, and radiation resistance. It is a key material to support the independent innovation and development and transformation and upgrading of new generation semiconductors, mobile communications, solar energy, new energy vehicles, rail transit, smart grids, aerospace and other industries. Silicon carbide has extremely high hardness (second only to diamond) and chemical inertness, which makes the precision processing of silicon carbide wafers very difficult, which leads to high processing costs and seriously restricts the industrial application of silicon carbide wafers. Silicon carbide polishing liquid is the main consumable in the chemical mechanical polishing process of silicon carbide wafers. Polishing liquid generally contains abrasives, oxidants, chelating agents, surfactants, pH regulators, corrosion inhibitors, etc. Abrasives are usually aluminum oxide, silicon oxide, and cerium dioxide, and oxidants are usually potassium permanganate, hydrogen peroxide, etc. Under the action of centrifugal force, the polishing liquid is evenly sprinkled on the surface of the polishing pad, reacts chemically with the surface of the silicon carbide wafer, and forms a softened layer; under the joint action of the abrasive and the polishing pad, the softened layer is removed by mechanical grinding, and the reaction products are taken out of the polishing pad to achieve the purpose of rapid and non-destructive removal. Obviously, the performance of the polishing liquid is a key factor affecting the quality and efficiency of chemical mechanical polishing. In order to obtain high polishing rate and surface quality at the same time, a perfect balance between chemical reaction and mechanical grinding must be achieved. The mechanical grinding effect of the abrasive is mainly determined by the physicochemical properties of the abrasive and its dispersion in the polishing liquid, while the chemical reaction depends on the oxidant, catalyst, pH value of the solution, etc. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a chemical mechanical polishing liquid containing molecular sieve particles in view of the deficiencies in the above-mentioned prior art.

[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is: a chemical mechanical polishing liquid containing molecular sieve particles is prepared by the following steps: S1, mixing molecular sieve particles with deionized water to obtain liquid A; S2, dissolving the oxidant in deionized water to obtain liquid B; S3, mixing liquid A and liquid B, adding an auxiliary agent, stirring evenly, and obtaining a polishing liquid.

[0007] Preferably, the molecular sieve is a molecular sieve material having a two-dimensional or three-dimensional pore structure from the molecular sieves defined by the International Zeolite Association, including but not limited to at least one of the following types of molecular sieves: type A, type X, type Y, mordenite, CHA, Beta, MFI, EMT, MCM-22, AlPO-18, SAPO-34.

[0008] Preferably, the molecular sieve is a hydrogen-type molecule or an alkali metal / alkaline earth metal ion-exchanged molecular sieve or a transition metal ion-exchanged molecular sieve or a rare earth metal ion-exchanged molecular sieve.

[0009] Preferably, the molecular sieve is at least one of a molecular sieve exchanged with sodium ions, potassium ions, calcium ions, magnesium ions, copper ions, nickel ions, cobalt ions, nickel ions, iron ions, manganese ions or zinc ions.

[0010] Preferably, the molecular sieve is a molecular sieve doped with framework elements, including at least one of TS-1, TS-2, Ti-Beta, Ti-Mor, Ti-MWW, Sn-Beta, Sn-MFI, Sn-MOR, Sn-MWW, and Sn-USY molecular sieves.

[0011] Preferably, the particle size of the molecular sieve particles is between 5 nanometers and 20 micrometers, and the BET specific surface area exceeds 100 square meters per gram.

[0012] Preferably, the oxidant is selected from one or more of permanganate, manganate, hydrogen peroxide, persulfate, cerium ammonium nitrate, periodic acid, chlorate, hypochlorite, bromate, ferrate, dichromate, and chromate; The additives include one or more of abrasive particles, dispersants, and pH regulators; The abrasive particles are selected from one or more of aluminum oxide, silicon dioxide, zirconium dioxide, titanium dioxide, silicon carbide, boron carbide, silicon nitride and diamond; The pH adjuster is selected from one or more of phosphoric acid, hydrogen phosphate, nitric acid, sulfuric acid, potassium hydroxide, sodium hydroxide, ammonia water, triethanolamine, oxalic acid, and amino acids.

[0013] Preferably, the concentration of the molecular sieve in the polishing liquid is 0.1-50 wt %, the pH of the polishing liquid is 1.0-14.0, and the molar concentration of the oxidant is 0.01-5.0 mol / L.

[0014] Preferably, the concentration of the molecular sieve in the polishing liquid is 2wt%, the pH of the polishing liquid is 4.0, the molecular sieve is any one of submicron Na-Y molecular sieve, submicron HY molecular sieve, nano Mn-Y molecular sieve, nano Cu-Beta molecular sieve, Sn-Beta molecular sieve, and the particle size of the submicron Na-Y molecular sieve and the submicron HY molecular sieve is 600-800 nanometers; Preferably, the concentration of the molecular sieve in the polishing liquid is 2wt%, the pH of the polishing liquid is 8.5, and the molecular sieve is any one of nano EMT molecular sieve, nano Cu-EMT molecular sieve, nano Cu-Beta molecular sieve, and Sn-Beta molecular sieve.

[0015] The present invention provides a novel chemical mechanical polishing liquid containing molecular sieve particles. In this polishing liquid, the molecular sieve acts as an abrasive or an abrasive and catalytic aid, which can significantly promote the reaction rate of the wafer material and the polishing liquid, thereby improving the polishing rate without affecting the surface quality. Molecular sieves are a type of aluminosilicate crystal materials with uniform molecular scale pores. The basic structure of the molecular sieve skeleton is SiO4 and AlO4 tetrahedrons, which are combined by shared oxygen atoms to form a three-dimensional network structure crystal. Depending on the different connection methods of SiO4 and AlO4 tetrahedrons, molecular sieves with different crystal structures will be formed. At present, more than 250 different molecular sieve crystal structures have been discovered (see the official website of the International Molecular Sieve Association, http: / / www.iza-online.org), and the common ones are A, X, Y, mordenite, MFI, Beta, CHA, LTL, silicon phosphorus aluminum type (SAPO-n series), phosphorus aluminum type (AlPO-n series), etc. Molecular sieves have adjustable acidity, high specific surface area, molecular-scale pores, unique adsorption properties and ion exchange capabilities. They are widely used in the petrochemical field as catalysts, adsorbents and ion exchangers.

[0016] After extensive research, the applicant of the present invention has found that certain types of molecular sieves can be used as abrasives or catalysts for chemical mechanical polishing of various materials, such as hard and brittle materials such as silicon carbide and silicon nitride, various metals and alloys, various polymer materials, etc. Under the same polishing conditions, the material removal rate using molecular sieves as abrasives is higher than that of traditional abrasives, such as α-Al2O3 abrasives and silica sol.

[0017] The present invention utilizes the acidity / alkalinity, high specific surface area and rich pore structure, ion exchange performance and skeleton element doping of molecular sieve to promote chemical action in chemical mechanical polishing, which can greatly improve the removal rate of various wafer materials. Compared with traditional inert abrasive grains, molecular sieve abrasive grains have adjustable acidity and alkalinity, which can significantly improve the oxidation rate of various wafer materials, thereby improving the removal rate. Molecular sieves have rich pore structures and high specific surface areas. Rich pore structures and high specific surface areas can provide more active sites, which are conducive to the adsorption of reactants and intermediates, thereby promoting the improvement of reaction rate; rich pore structures are conducive to the mass transfer and diffusion of reactants and intermediates, reducing or even eliminating mass transfer bottlenecks, and improving reaction rates. The hardness of molecular sieve materials is relatively low (the hardness is only 3~5, which is much lower than the commonly used α-Al2O3 abrasive grains), and it will not scratch the wafer. The polished wafer has a high surface flatness. Introducing transition metal ions into the skeleton and pores of the molecular sieve by means of skeleton doping and ion exchange can play a catalytic role and promote the removal of wafer materials. Transition metal ions have variable valence and are an extremely important type of catalyst, which is widely used in the field of petrochemicals. The particle size of molecular sieves can be controlled in the range of tens of nanometers to micrometers, and the particle size distribution is narrow, which is conducive to reducing scratches. Molecular sieves are low-priced, do not pollute the environment, and are conducive to industrial applications.

[0018] The beneficial effects of the present invention are: (1) The present invention provides a chemical mechanical polishing liquid containing molecular sieve particles. The present invention utilizes the acidity / alkalinity, high specific surface area and rich pore structure, ion exchange performance and doping of molecular sieve framework elements of the molecular sieve to promote the chemical reaction in chemical mechanical polishing, which can greatly improve the removal rate of various wafer materials.

[0019] (2) Molecular sieves are highly acidic and can significantly increase the oxidation rate of a variety of wafer materials, thereby increasing the removal rate; molecular sieves have a high specific surface area and a rich pore structure. The high specific surface area can provide more active sites, which is conducive to the adsorption of reactants; and the rich pore structure is conducive to the mass transfer and diffusion of reactants, reducing mass transfer bottlenecks. Introducing transition metal ions into the skeleton and pores of molecular sieves through skeleton doping and ion exchange can play a catalytic role and promote the oxidation and removal of wafer materials; the particle size of molecular sieves can be controlled at a scale of tens of nanometers to microns, and the particle size distribution is narrow, which is conducive to reducing scratches. Molecular sieves are inexpensive, do not pollute the environment, and are conducive to industrial applications.

[0020] (3) In the preferred chemical mechanical polishing liquid of the present invention, by using a specific type of molecular sieve as an abrasive and matching it with a polishing liquid system with a suitable pH value, a removal rate higher than or equivalent to that of commercial α-Al2O3 can be obtained. However, compared with commercial α-Al2O3, the hardness of the molecular sieve material is lower (the hardness is only 3 to 5, which is much lower than the commonly used α-Al2O3 abrasive). The molecular sieve as an abrasive also has the advantages of not scratching the wafer and the wafer after polishing has a higher surface flatness. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 is the XRD diffraction pattern of commercial Na-Y; Figure 2 This is a scanning electron microscope (SEM) image of commercial Na-Y; Figure 3 This is the XRD diffraction pattern of commercial nano-scale sodium-type Y molecular sieve; Figure 4 This is a scanning electron microscope (SEM) photo of commercial nanoscale sodium-type Y molecular sieve; Figure 5 is the XRD diffraction pattern of nano MY molecular sieve; Figure 6 This is the XRD diffraction pattern of nano-scale sodium-type EMT molecular sieve; Figure 7 This is a scanning electron microscope (SEM) photo of the nanoscale sodium-type EMT molecular sieve; Figure 8 is the XRD diffraction pattern of Silicalite-1 molecular sieve; Fig. 9 This is a scanning electron microscope (SEM) photo of Silicalite-1 molecular sieve; Fig.10 is the XRD diffraction pattern of commercial Beta molecular sieve; Fig.11 This is a scanning electron microscope (SEM) photo of commercial Beta molecular sieve; Fig.12 is the XRD diffraction pattern of commercial SAPO-34 molecular sieve; Fig.13 This is a scanning electron microscope (SEM) photo of commercial SAPO-34 molecular sieve; Fig.14 This is a scanning electron microscope (SEM) photo of commercial AlPO-18 molecular sieve; Fig.15 is the XRD diffraction pattern of commercial Na-A molecular sieve; Fig.16 This is a scanning electron microscope (SEM) photo of commercial Na-A molecular sieve; Fig.17It is the XRD diffraction pattern of commercial TS-1 molecular sieve; Fig.18 This is a scanning electron microscope (SEM) photo of commercial TS-1 molecular sieve; Fig.19 is the XRD diffraction pattern of commercial Sn-Beta molecular sieve; Fig. 20 This is a scanning electron microscope (SEM) photo of commercial Sn-Beta molecular sieve; Fig.21 and Fig. 22 They are the XRD diffraction pattern and SEM photo of ZSM-23 sample respectively. DETAILED DESCRIPTION

[0022] The present invention is further described in detail below in conjunction with embodiments so that those skilled in the art can implement the invention with reference to the description.

[0023] It should be understood that the terms such as “having”, “including” and “comprising” used herein do not exclude the existence or addition of one or more other elements or combinations thereof.

[0024] The test methods used in the following examples are conventional methods unless otherwise specified. The materials and reagents used in the following examples are all commercially available unless otherwise specified. In the following examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not specified, are all conventional products that can be purchased commercially.

[0025] Example 1: Commercial α-Al2O3 nanoparticles and commercial silica sol for polishing of silicon carbide wafers Example 1 is a control test, using commercial α-Al2O3 nanoparticles (rough polishing of silicon carbide wafers) and commercial silica sol (fine polishing of silicon carbide wafers) as abrasives. The commercial α-Al2O3 nanoparticles are provided by Henan Tianma New Materials, model LA-T, and particle size is about 0.5 μm. The commercial silica sol is provided by Shandong Better New Materials, model LS60C40, and particle size is about 70 nanometers.

[0026] 1.1. The preparation steps of the rough polishing liquid using commercial α-Al2O3 nanoparticles as abrasive are as follows: Step 1: Weigh 20.0 g of α-Al2O3 nanoparticles and mix with 380 g of deionized water to obtain liquid A.

[0027] Step 2: Weigh 20.0 g of potassium permanganate and dissolve it in 580 g of deionized water to obtain liquid B.

[0028] Step 3: Stir and mix liquid A and liquid B, add an appropriate amount of potassium hydroxide solution to adjust the pH to 8.5, and obtain a polishing liquid.

[0029] Finally, 1000 g of polishing liquid was obtained, in which the concentration of abrasive (α-Al2O3 nanoparticles) was 2.0%, the concentration of potassium permanganate was 2.0%, and the pH value of the polishing liquid was 8.5. If polishing at other pH values ​​is required, the amount of potassium hydroxide added can be changed, or the pH value can be adjusted to acidic with dilute nitric acid. For example, the polishing liquid with a pH value of 4.0 in the following text is adjusted by adding dilute nitric acid (concentration of 10wt%).

[0030] 1.2. The preparation steps of fine polishing liquid with commercial silica sol as abrasive are as follows: Step 1: Weigh 200 g of silica sol (30 wt% concentration, particle diameter 60 nm) and mix it with 200 g of deionized water to obtain liquid A.

[0031] Step 2: Weigh 20.0 g of potassium permanganate and dissolve it in 580 g of deionized water to obtain liquid B.

[0032] Step 3: Stir and mix liquid A and liquid B, add an appropriate amount of potassium hydroxide solution to adjust the pH to 8.5, and obtain a polishing liquid.

[0033] Finally, 1000 grams of polishing liquid was obtained, in which the concentration of silica sol abrasive was 6.0%, the concentration of potassium permanganate was 2.0%, and the pH value of the polishing liquid was 8.5. If polishing at other pH values ​​is required, the amount of potassium hydroxide added can be changed, or the pH value can be adjusted to acidic with dilute nitric acid. For example, the polishing liquid with a pH value of 4.0 in the following text is obtained by adding dilute nitric acid (concentration of 10wt%). It is worth pointing out that the final silica sol concentration can be controlled by changing the amount of silica sol added in step 1.

[0034] 1.3. The wafer used for polishing is a 4-inch conductive silicon carbide wafer (polishing the silicon surface of the silicon carbide wafer). The polishing conditions are shown in Table 1.1: Table 1.1 Polishing conditions

[0035] The material removal rate (MRR) is calculated as follows:

[0036] Where Δm (g) is the weight loss of the SiC wafer during the polishing process, and ρ is the density of SiC (ρ = 3.2 g / cm 3 ), t is the polishing time (t = 1 h), and r is the radius of the SiC wafer (r = 10.16 cm).

[0037] Table 1.2 shows the removal rate of α-Al2O3 abrasive and silica sol abrasive on silicon-silicon carbide wafers at different pH values. It can be seen that under the same polishing conditions, the removal rate of α-Al2O3 abrasive is higher than that of silica sol, which is attributed to the high hardness and large particle size of α-Al2O3 abrasive, and the high removal rate; but the disadvantage is that the surface quality and flatness are poor, and only rough polishing can be done. Silica sol abrasive has low hardness and small particle size, and the surface quality of the wafer after polishing is high, but the removal rate is low. For the same abrasive, the removal rate is higher at low pH, which is attributed to the stronger oxidizing property of potassium permanganate under acidic conditions, resulting in a higher removal rate.

[0038] Table 1.2 Removal rate of α-Al2O3 and silica sol abrasives on silicon surface-SiC wafer

[0039] As shown in Table 1.2, whether at pH 4.0 or 8.5, the polishing rate increases with the increase of silica sol concentration, and reaches the maximum value at 6%. As the silica sol concentration continues to increase, the removal rate decreases slightly (data not listed). This rule is consistent with the literature data, that is, under fixed polishing conditions, the removal rate has this maximum value as the concentration changes. Correspondingly, with 2% commercial α-Al2O3 as abrasive, its removal rate far exceeds that of 2% silica sol abrasive under the same conditions (about 4 times higher), and even exceeds that of 6% silica sol abrasive. This is due to the high hardness and large particles of α-Al2O3 abrasive, which leads to a strong mechanical scraping effect. Currently, commercial silicon carbide polishing liquids mostly use 2% α-Al2O3 abrasives (as rough polishing liquid, with high removal rate but poor surface quality) or 6% silica sol abrasives (as fine polishing liquid, with low removal rate but high surface quality). Therefore, the abrasive of this patent is also compared with commercial α-Al2O3 abrasive and silica sol abrasive using a concentration of 2%.

[0040] Example 2: Polishing of Silicon Carbide Wafers with Y Molecular Sieve Example 2 The polishing liquid is prepared by replacing the abrasive (α-Al2O3 nanoparticles) in Example 1 with sodium-type and hydrogen-type Y molecular sieves (i.e., Na-Y and HY molecular sieves, commercial molecular sieves) of the same mass to polish the silicon carbide wafer. The particle size of the Y molecular sieve here is submicron, about 600-800 nanometers.

[0041] The only difference from 1.1 of Example 1 is that the 20.0 g of α-Al2O3 abrasive in step 1 is replaced by 20.0 g of Y molecular sieve (sodium type or hydrogen type Y molecular sieve), and the rest is the same as Example 1. The Y molecular sieve used here is a commercially available Y molecular sieve with a particle size of 600-800 nanometers. The crystal structure of the Y molecular sieve is a FAU structure, which is a large-pore molecular sieve with a three-dimensional pore structure and a pore size of 0.73 nanometers.

[0042] Figure 1 , Figure 2 They are the XRD diffraction pattern and scanning electron microscope (SEM) photo of commercial Na-Y. It can be seen that its XRD diffraction pattern is consistent with the standard Y molecular sieve diffraction pattern, indicating that it is a pure phase Y molecular sieve. The SEM photo shows that the Na-Y molecular sieve has a polyhedral particle morphology with a uniform particle size distribution of about 600~800 nanometers. The hydrogen-type Y molecular sieve is made from commercial Na-Y molecular sieve by ion exchange. Its morphology does not change, and the XRD diffraction pattern is almost exactly the same. Therefore, the XRD diffraction pattern and scanning electron microscope photo of the hydrogen-type Y molecular sieve are not provided. The BET specific surface areas of NaY and HY molecular sieves are 576 m 2 / g and 598 m 2 / g.

[0043] At a concentration of 2%, the polishing liquid has a removal rate of 0.79 μm / h (pH=4) and 0.49 μm / h (pH=8.5) for silicon-SiC wafers, which is significantly higher than the silica sol abrasive of the same concentration (even higher than the silica sol abrasive of 6%), and is similar to the α-Al2O3 abrasive (see Table 2.1). Using molecular sieve as abrasive, the surface flatness of the wafer after polishing is also comparable to that of silica sol abrasive, and significantly better than that of α-Al2O3 abrasive. In view of the small particle size and lower hardness of Na-Y molecular sieve, it is more suitable as an abrasive for fine polishing liquid. In other words, Na-Y molecular sieve is a better abrasive than silica sol, with a higher removal rate and comparable surface flatness under the same polishing conditions. Na-Y molecular sieve has strong alkalinity and has a strong etching effect on silicon carbide wafers, so it has a higher removal rate than inert α-Al2O3 and silica sol abrasives. After exchanging the sodium ions in the Na-Y molecular sieve for hydrogen ions (HY molecular sieve), the removal rate increased. This indicates that the acidity of the molecular sieve promotes the polishing of silicon carbide, because potassium permanganate is more oxidizing under acidic conditions, which increases the oxidation rate of silicon carbide, resulting in a higher removal rate.

[0044] Table 2.1 Removal rate of Y molecular sieve abrasive on silicon surface-silicon carbide wafer

[0045] The surface morphology and roughness of the polished silicon carbide wafer were analyzed using a three-dimensional optical profiler (Sensofar S-neox 090, using phase-shift interferometry mode). The sampling area was 10 μm×10 μm, and the average value of 5 points for each sample was calculated. The results are shown in Table 2.1 above. It can be seen that the surface flatness of the wafer is significantly worse than that of the silica sol and molecular sieve abrasives with lower hardness when polished with α-Al2O3 abrasives with high hardness. The hardness of different abrasives is shown in Table 2.2. In the field of polishing, abrasives with high hardness (such as diamond, α-Al2O3, etc.) are usually used for initial polishing, taking advantage of their high removal rate; and then silica sol abrasives with low hardness are used for fine polishing, taking advantage of the high surface flatness of the wafer after polishing. The molecular sieve abrasive of the present invention takes into account both high removal rate and high surface flatness, and has greater advantages than traditional abrasives.

[0046] Table 2.2 Density and hardness of different abrasives

[0047] Example 3: Polishing of Silicon Carbide Wafers by Nano-Scale Y Molecular Sieve Example 3: The α-Al2O3 abrasive in Example 1 is replaced by nano-scale sodium-type Y molecular sieve (i.e., nano-Na-Y molecular sieve) of the same mass to polish the silicon carbide wafer. The particle size of the nano-Na-Y molecular sieve is about 70 nanometers.

[0048] The only difference from 1.1 of Example 1 is that the 20.0 g of α-Al2O3 abrasive in step 1 is replaced by 20.0 g of nano-grade sodium-type Y molecular sieve (sodium-type or hydrogen-type Y molecular sieve), and the rest is the same as Example 1. The nano-grade sodium-type Y molecular sieve used here is a commercially available Y molecular sieve with a particle size of about 70 nanometers. The crystal structure of the Y molecular sieve is a FAU structure, which is a large-pore molecular sieve with a three-dimensional pore structure and a pore size of 0.73 nanometers.

[0049] Figure 3 , Figure 4 They are the XRD diffraction pattern and scanning electron microscope (SEM) photo of commercial nano-scale sodium-type Y molecular sieve. It can be seen that its XRD diffraction pattern is consistent with the standard card, indicating that it is a pure phase Y molecular sieve. The SEM photo shows that the Na-Y molecular sieve is a polyhedral particle morphology with a uniform particle size distribution of about 70 nanometers. The BET specific surface areas of nano-scale NaY and the submicron-scale Na-Y molecular sieve in Example 2 are 615 m 2 / g and 576 m 2 / g.

[0050] The removal rate of the polishing liquid for silicon-SiC wafers is 0.62 μm / h (pH=4) and 0.48 μm / h (pH=8.5), which is significantly lower than that of α-Al2O3 abrasives at the same concentration of silica sol abrasives (even higher than 6% concentration of silica sol abrasives) (Table 3.1). In view of the small particle size and lower hardness of the nano-scale sodium-type Y molecular sieve, it is more suitable as an abrasive for fine polishing liquid, that is, the nano-scale Na-Y molecular sieve is a better abrasive than silica sol. In addition, compared with the submicron Na-Y molecular sieve abrasive in Example 2, the removal rate of the nano-Na-Y molecular sieve is slightly lower (the mechanical scraping effect of small particles is weaker), but the suspension stability of the nano-Na-Y molecular sieve is better, and the surface flatness of the silicon carbide wafer is also better, as shown in Table 3.1.

[0051] Table 3.1. Removal rate of Y molecular sieve abrasive on silicon surface-SiC wafer

[0052] Example 4: Polishing of Silicon Carbide Wafers Using Ion-Exchanged Y Molecular Sieve Example 4 The α-Al2O3 abrasive in Example 1 is replaced by a Y molecular sieve (i.e., nano-MY molecular sieve, where M can be any transition metal ion, such as copper, manganese, iron, zinc, etc.) of the same mass to polish the silicon carbide wafer. The particle size of the nano-Na-Y molecular sieve here is about 70 nanometers.

[0053] The only difference from 1.1 of Example 1 is that the 20.0 g of α-Al2O3 abrasive in step 1 is replaced by 20.0 g of nano-scale transition metal ion exchanged Y molecular sieve (MY molecular sieve), and the rest is the same as Example 1. The nano-scale transition metal ion exchanged Y molecular sieve used here is the nano-Y molecular sieve used in Example 3 obtained by ion exchange, and the particle size is about 70 nanometers. The BET specific surface areas of the Cu-Y molecular sieve and Mn-Y after ion exchange are 480 m 2 / g and 473m 2 / g.

[0054] The XRD spectrum of nano MY molecular sieve after ion exchange is as follows: Figure 5As shown, the scanning electron microscope photos are not listed because the ion exchange has no effect on the morphology of the crystal, which is almost exactly the same as the nanoscale Na-Y molecular sieve in Example 3. The removal rate of the polishing liquid of Cu-Y molecular sieve as abrasive for silicon surface-silicon carbide wafer is 0.76 μm / h (pH=4) and 0.58 μm / h (pH=8.5). The removal rate of the polishing liquid of Mn-Y molecular sieve as abrasive for silicon surface-silicon carbide wafer is 0.82 μm / h (pH=4) and 0.59 μm / h (pH=8.5). It can be seen that the removal rate of Y molecular sieve exchanged with transition metal ions is significantly higher than that of silica sol abrasives, and is similar to that of α-Al2O3 abrasives (Table 4.1). Compared with nano Na-Y molecular sieve, the introduction of transition metal ions can significantly increase the oxidation rate of silicon carbide, which is related to the variable valence of transition metal ions. According to traditional catalytic theory, transition metals have d-orbital electrons or empty d-orbitals, and can act as electrophiles or nucleophiles in chemical reactions to form intermediates, thereby reducing the activation energy of the reaction and promoting the reaction. In addition, transition metal oxides also have strong redox properties, semiconductor properties, and the splitting characteristics of the inner valence orbital and the outer orbital, so they are often used as redox reaction catalysts. Literature reports also show that the addition of transition metal ions can significantly enhance the oxidation ability of potassium permanganate and greatly increase the removal rate of silicon carbide wafers (ECS Journal of Solid State Science and Technology, 3 (6) P219-P225 (2014)). Given the small particle size and low hardness of nano-scale Y molecular sieve, it is more suitable as an abrasive for fine polishing liquid, that is, nano-scale transition metal ion-exchanged MY molecular sieve is a better abrasive than silica sol.

[0055] Table 4.1. Removal rate of Cu-Y molecular sieve abrasive on silicon surface-SiC wafer

[0056] Example 5: Polishing of silicon carbide wafers using EMT molecular sieves Example 5 uses nano-scale sodium EMT molecular sieve (i.e., nano-scale Na-EMT) and copper ion exchanged EMT (i.e., nano-scale Cu-EMT) of the same mass to replace the abrasive (α-Al2O3 nanoparticles) in Example 1, that is, nano-scale sodium EMT molecular sieve is used as abrasive to polish silicon carbide wafers. The particle size of the EMT molecular sieve here is nano-scale, about 70 nanometers.

[0057] The only difference from 1.1 of Example 1 is that the 20.0 g of α-Al2O3 abrasive in step 1 is replaced with 20.0 g of nano-sodium EMT molecular sieve, and the rest is the same as Example 1. The nano-sodium EMT molecular sieve used here is a commercially available EMT molecular sieve with a particle size of about 70 nanometers. The crystal structure of the EMT molecular sieve is an EMT structure, which is a macroporous molecular sieve with a three-dimensional pore structure and a pore size of 0.73 nanometers.

[0058] Figure 6 , Figure 7 They are the XRD diffraction pattern and scanning electron microscope (SEM) photos of the nanoscale sodium EMT molecular sieve. It can be seen that its XRD diffraction pattern is consistent with the standard EMT diffraction pattern, indicating that it is a pure phase EMT molecular sieve. The SEM photo shows that the particle size distribution of the EMT molecular sieve is uniform and less than 100 nanometers. The transmission electron microscope photo shows that the EMT crystal has a hexagonal flake morphology with a crystal diameter between 30 and 100 nanometers. The BET specific surface areas of Na-EMT and Cu-EMT molecular sieves are 482 m 2 / g and 456 m 2 / g. The removal rates of the polishing liquid with nano-scale Na-EMT molecular sieve as abrasive for silicon surface-silicon carbide wafers are 0.74 μm / h (pH=4) and 0.62 μm / h (pH=8.5). The removal rates of the polishing liquid with nano-scale Cu-EMT molecular sieve as abrasive for silicon surface-silicon carbide wafers are 0.78 μm / h (pH=4) and 0.66 μm / h (pH=8.5). The removal rates of both are significantly higher than those of silica sol abrasives and are similar to those of α-Al2O3 abrasives (Table 5.1). In view of the small particle size and lower hardness of EMT molecular sieve, it is more suitable as an abrasive for fine polishing liquid, that is, EMT molecular sieve is a better abrasive than silica sol.

[0059] Table 5.1 Removal rate of EMT molecular sieve abrasive on silicon surface-silicon carbide wafer

[0060] Example 6: Polishing of Silicon Carbide Wafers Using Silicalite-1 Molecular Sieve Example 6: The α-Al2O3 abrasive in Example 1 is replaced by nano-Silicalite-1 molecular sieve of the same mass, that is, the nano-Silicalite-1 molecular sieve is used as the abrasive to polish the silicon carbide wafer. The particle size of the Silicalite-1 molecular sieve here is nanometer-level, about 70 nanometers.

[0061] The only difference from 1.1 of Example 1 is that the 20.0 g of α-Al2O3 abrasive in step 1 is replaced by 20.0 g of nano-Silicalite-1 molecular sieve, and the rest is the same as Example 1. The Silicalite-1 molecular sieve used here is a commercially available Silicalite-1 molecular sieve with a particle size of about 80 nanometers. The crystal structure of the Silicalite-1 molecular sieve is an MFI structure, which is a full-silicon mesoporous molecular sieve. The molecular sieve with an MFI structure has a two-dimensional pore structure with a pore size of 0.55 nanometers. Compared with traditional silicon-aluminum molecular sieves, the full-silicon molecular sieve is characterized by no acidity and the molecular sieve crystals are hydrophobic. The full-silicon molecular sieve has high thermal stability and chemical stability (acid and alkali resistance) and can be used in harsh environments.

[0062] Figure 8 , Fig. 9 These are the XRD diffraction pattern and scanning electron microscope (SEM) photos of Silicalite-1 molecular sieve. It can be seen that its XRD diffraction pattern is consistent with the standard card, indicating that it is a pure phase Silicalite-1 molecular sieve. The SEM photo shows that the particle size distribution of Silicalite-1 molecular sieve is uniform, about 80 nanometers. The BET specific surface area of ​​this molecular sieve is 421 m 2 / g. The removal rate of the polishing liquid for silicon-silicon carbide wafers is 0.54 μm / h (pH=4) and 0.46 μm / h (pH=8.5), which is higher than the silica sol abrasive of the same concentration at pH=8.5 (see Table 6.1, equivalent to 6% concentration of silica sol abrasive). In view of the small particle size and lower hardness of Silicalite-1 molecular sieve, it is more suitable as an abrasive for fine polishing liquid, that is, Silicalite-1 molecular sieve is a better abrasive than silica sol.

[0063] Table 6.1 Removal rate of Silicalite-1 molecular sieve abrasive on silicon surface-silicon carbide wafer

[0064] Example 7: Polishing of Silicon Carbide Wafers with Beta Molecular Sieve In Example 7, the α-Al2O3 abrasive in Example 1 is replaced by nano-scale hydrogen-type Beta molecular sieve (nano H-Beta molecular sieve), nano-scale sodium-type Beta molecular sieve (nano Na-Beta molecular sieve) and nano-scale copper ion exchange Beta molecular sieve (nano Cu-Beta molecular sieve) of the same mass, that is, the above three Beta molecular sieves are used as abrasives for polishing silicon carbide wafers. The Na-Beta molecular sieve and the Cu-Beta molecular sieve are obtained by ion exchange of the H-Beta molecular sieve.

[0065] The only difference is that the 20.0 g of α-Al2O3 abrasive in step 1 is replaced by 20.0 g of nano-scale H-Beta molecular sieve (hydrogen-type Beta molecular sieve), and the rest is the same as Example 1. The H-Beta molecular sieve used here is a commercially available H-Beta molecular sieve with a particle size of about 100 nanometers and a silicon-aluminum ratio of about 20. The crystal structure of Beta molecular sieve is a BEA structure. Beta molecular sieve is a large-pore molecular sieve with a three-dimensional pore structure and a pore size of 0.69 nanometers. The BET specific surface areas of the H-Beta molecular sieve, Na-Beta molecular sieve and Cu-Beta molecular sieve used here are 645 m 2 / g, 623 m 2 / g and 584 m 2 / g.

[0066] Fig.10 , Fig.11 They are the XRD diffraction pattern and scanning electron microscope (SEM) photo of commercial Beta molecular sieve. It can be seen that its XRD diffraction pattern is consistent with the standard card, indicating that it is a pure phase Beta molecular sieve. The XRD diffraction pattern of the Beta molecular sieve exchanged with copper ions is basically the same as that of the non-ion exchanged one. The SEM photo shows that the Beta molecular sieve is a nearly spherical nanoparticle with a uniform particle size distribution of about 70 nanometers. As shown in Table 7.1, the removal rate of the polishing liquid with H-Beta molecular sieve as abrasive for silicon surface-silicon carbide wafer is 0.74 μm / h (pH=4) and 0.58 μm / h (pH=8.5). Under the same conditions, the removal rate of H-Beta molecular sieve is slightly lower, while the removal rate of Cu-Beta molecular sieve is the highest. The removal rates of the three are significantly higher than those of silica sol abrasives, but slightly lower than those of α-Al2O3 abrasives (Table 7.1). In view of the ultra-small particle size and small hardness of Beta molecular sieve, it is more suitable as an abrasive for fine polishing liquid.

[0067] Table 7.1 Removal rate of Beta molecular sieve abrasive on silicon surface-silicon carbide wafer

[0068] Example 8: Polishing of Silicon Carbide Wafers with SAPO-34 Molecular Sieve In Example 8, the abrasive (α-Al2O3 nanoparticles) in Example 1 is replaced by hydrogen-type SAPO-34 molecular sieve (H-SAPO-34 molecular sieve) of the same mass, that is, hydrogen-type SAPO-34 molecular sieve is used as abrasive to polish silicon carbide wafers.

[0069] The only difference is that the 20.0 g of abrasive particles (α-Al2O3 nanoparticles) in step 1 are replaced by 20.0 g of H-SAPO-34 molecular sieve (hydrogen-type SAPO-34 molecular sieve), and the rest is the same as Example 1. The H-SAPO-34 molecular sieve used here is a commercially available H-SAPO-34 molecular sieve with a particle size of submicron. The crystal structure of SAPO-34 molecular sieve is CHA structure, which is a silicon-phosphorus-aluminum type molecular sieve and a small-pore molecular sieve with a three-dimensional pore structure and a pore size of 0.38 nanometers.

[0070] Fig.12 , Fig.13 They are the XRD diffraction pattern and scanning electron microscope (SEM) photo of commercial SAPO-34 molecular sieve. It can be seen that its XRD diffraction pattern is consistent with the standard card, indicating that it is a pure phase SAPO-34 molecular sieve. The SEM photo shows that the SAPO-34 molecular sieve is a nearly cubic submicron particle with a uniform particle size distribution of about 800 nanometers. The BET specific surface area of ​​the molecular sieve is 561m 2 / g. As shown in Table 8.1, the removal rate of the polishing liquid for silicon-SiC wafers is 0.43 μm / h (pH=4) and 0.35 μm / h (pH=8.5), which is higher than the 2% concentration of silica sol abrasive, and lower than the 6% concentration of silica sol abrasive, but lower than α-Al2O3 abrasive (Table 8.1). In view of the small particle size and lower hardness of SAPO-34 molecular sieve, it is more suitable as an abrasive for fine polishing liquid.

[0071] Table 8.1 Removal rate of SAPO-34 molecular sieve abrasive on silicon surface-silicon carbide wafer

[0072] Example 9: Polishing of Silicon Carbide Wafers with AlPO-18 Molecular Sieve In Example 9, the α-Al2O3 abrasive in Example 1 is replaced with AlPO-18 molecular sieve of the same mass to polish the silicon carbide wafer.

[0073] The only difference from 1.1 of Example 1 is that the 20.0 g of α-Al2O3 abrasive in step 1 is replaced by 20.0 g of AlPO-18 molecular sieve, and the rest is the same as Example 1. The H-SAPO-34 molecular sieve used here is a commercially available AlPO-18 molecular sieve with a particle size of submicron. The crystal structure of AlPO-18 molecular sieve is AEI structure, which is a phosphorus aluminum type molecular sieve and also a small pore molecular sieve with a three-dimensional pore structure and a pore size of 0.38 nanometers. It is worth pointing out that AlPO-18 molecular sieve has no proton acidity.

[0074] Fig.14This is a scanning electron microscope (SEM) photo of commercial AlPO-18 molecular sieve. The SEM photo shows that AlPO-18 molecular sieve is a thin flaky crystal with a crystal diameter of 400-800 nanometers and a thickness of about 50 nanometers. The BET specific surface area of ​​this molecular sieve is 485 m 2 / g.

[0075] Table 9.1 Removal rate of AlPO-18 molecular sieve abrasive on silicon surface-silicon carbide wafer

[0076] As shown in Table 9.1, the removal rate of the polishing liquid for silicon-SiC wafer is 0.43 μm / h (pH=4) and 0.35 μm / h (pH=8.5), which is higher than the 2% concentration of silica sol abrasive, but lower than the 6% concentration of silica sol abrasive), but lower than α-Al2O3 abrasive. In view of the small particle size and lower hardness of AlPO-18 molecular sieve, it is more suitable as an abrasive for fine polishing liquid.

[0077] Example 10: Polishing of silicon carbide wafers using Na-A molecular sieves In Example 10, Na-A molecular sieve of the same mass is used to replace the α-Al2O3 abrasive in Example 1 to polish the silicon carbide wafer.

[0078] The only difference from 1.1 of Example 1 is that the 20.0 g of α-Al2O3 abrasive in step 1 is replaced by 20.0 g of Na-A molecular sieve, and the rest is the same as Example 1. The Na-A molecular sieve used here is a commercially available Na-A molecular sieve with a particle size of nanometers and no more than 300 nanometers. The crystal structure of Na-A molecular sieve is LTA structure, which is a hydrophilic silicon-aluminum type molecular sieve with a three-dimensional pore structure. It is a small-pore molecular sieve with a pore size of 0.38 nanometers.

[0079] Fig.15 , Fig.16 This is the XRD diffraction pattern and scanning electron microscope (SEM) photo of commercial Na-A molecular sieve. It can be seen that its XRD diffraction pattern is consistent with the standard card, indicating that it is pure phase Na-A molecular sieve. The SEM photo shows that Na-A molecular sieve is cubic or nearly spherical crystals with a crystal diameter of no more than 300 nanometers, and a large number of crystals have a diameter of less than 100 nanometers. The BET specific surface area of ​​this molecular sieve is 354 m 2 / g.

[0080] Table 10.1 Removal rate of Na-A molecular sieve abrasive on silicon surface-silicon carbide wafer

[0081] As shown in Table 10.1, the removal rate of the polishing liquid for silicon-silicon carbide wafers is 0.66 μm / h (pH=4) and 0.52 μm / h (pH=8.5), which is significantly higher than silica sol abrasive and nano Na-Y molecular sieve abrasive, but lower than α-Al2O3 abrasive. In view of the small particle size and lower hardness of Na-A molecular sieve, it is more suitable as an abrasive for fine polishing liquid.

[0082] Example 11 Polishing of GaN Wafers with Molecular Sieve Abrasives Example 11 is similar to Example 4, the only difference is that the silicon surface-silicon carbide wafer is replaced with a gallium nitride wafer. That is, nano Na-Y molecular sieve is used as an abrasive to polish the gallium nitride wafer. Gallium nitride and silicon carbide are both third-generation semiconductor materials and are widely used in integrated circuits, power devices, 5G communications and other fields. As shown in Table 11.1, the removal rate of the polishing liquid for gallium nitride wafers is 0.46 μm / h (pH=4) and 0.35 μm / h (pH=8.5), which is much higher than the silica sol abrasive of the same concentration, and is close to the removal rate of α-Al2O3 abrasive. In view of the small particle size and lower hardness of Na-Y molecular sieve, it is more suitable as an abrasive for gallium nitride polishing liquid.

[0083] Table 11.1 Removal rate of Na-Y molecular sieve abrasive on GaN wafer

[0084] Example 12: Polishing of aluminum alloy with molecular sieve abrasive Example 12 is to polish aluminum alloy (6063 aluminum alloy) with different abrasives. The aluminum alloy sample is a circular thin slice with a diameter of 1.5 cm. The preparation steps of the polishing liquid are as follows (using silica sol abrasive as an example, the preparation steps of the polishing liquid of other abrasives are the same), and the polishing conditions are shown in Table 12.1.

[0085] Preparation of polishing liquid with silica sol as abrasive: 1. Dilute the commercial silica sol (particle size 60 nanometers, concentration 40% SiO2) to 20% and stir evenly; 2. Add appropriate amount of hydrogen peroxide solution and stir evenly; 3. Add appropriate amount of complexing agent malonic acid and stir evenly; 4. Add appropriate amount of potassium hydroxide to adjust the pH to 10.0.

[0086] The final polishing liquid composition is 20% silica sol, 1.0% hydrogen peroxide, 0.1% malonic acid, and the pH value of the polishing liquid is 10.0.

[0087] Table 12.1 Polishing conditions of aluminum alloy (6063)

[0088] The EMT molecular sieve here is the same as the EMT molecular sieve in Example 5. The Beta molecular sieve here is the same as the Beta molecular sieve in Example 7. As can be seen from Table 12.2, the removal rate of the Beta molecular sieve is much higher than that of the traditional silica sol abrasive, even when the concentration of the Beta molecular sieve is lower than that of the silica sol.

[0089] Table 12.2 Removal rate of different abrasives on aluminum alloy (6063)

[0090] Example 13: Polishing of titanium alloy with molecular sieve abrasive Example 13 compares the polishing of TC4 titanium alloy by different abrasives. The TC4 titanium alloy sample is a circular thin slice with a diameter of 1.5 cm. The polishing conditions are shown in Table 13.1. The composition of the polishing liquid is 2.0% abrasive, 2.0% H2O2 as an oxidant, and 0.02% citric acid as a complexing agent. The pH of the polishing liquid can be adjusted by adding nitric acid or potassium hydroxide. Table 13.2 lists the removal rates of titanium alloy polished by different abrasives. It can be seen that under the same polishing conditions, the removal rate of Beta molecular sieve is higher than that of the currently commonly used silica sol abrasive. The EMT molecular sieve here is the same as the EMT molecular sieve in Example 5. The Beta molecular sieve here is the same as the Beta molecular sieve in Example 7. The Y molecular sieve here is the same as the Y molecular sieve in Example 3.

[0091] Table 13.1 Polishing conditions of titanium alloy (TC4)

[0092] Table 13.2 Removal rate of different abrasives on titanium alloy (TC4)

[0093] Example 14: Polishing of Stainless Steel (304) with Molecular Sieve Abrasives Example 14 is the polishing of 304 stainless steel with different abrasives. The sample is a circular slice with a diameter of 1.5 cm. The polishing conditions are shown in Table 14.1. The composition of the polishing liquid is 2.0% abrasive, 0.020% H2O2 as an oxidant, and 0.008% citric acid as a complexing agent. The pH of the polishing liquid can be adjusted by adding nitric acid or potassium hydroxide. Table 14.2 lists the removal rates of 304 stainless steel polished with different abrasives. It can be seen that under the same polishing conditions, the removal rate of Beta molecular sieve is higher than that of the currently commonly used silica sol abrasive.

[0094] Table 14.1 Polishing conditions of stainless steel (304)

[0095] Table 14.2 Removal rate of 304 stainless steel by different abrasives

[0096] Example 15: TS-1 molecular sieve (titanium silicate molecular sieve) as abrasive In Example 15, TS-1 molecular sieve (titanium silicon molecular sieve) of the same mass is used to replace the α-Al2O3 abrasive in Example 1 to polish the silicon carbide wafer.

[0097] The only difference from 1.1 of Example 1 is that the 20.0 g of α-Al2O3 abrasive in step 1 is replaced by 20.0 g of TS-1 molecular sieve, and the rest is the same as Example 1. The TS-1 molecular sieve used here is a commercially available TS-1 molecular sieve with a particle size of nanometers and not more than 300 nanometers. The crystal structure of the TS-1 molecular sieve is an MFI structure, which is a hydrophobic titanium silicon type molecular sieve (does not contain aluminum). The TS-1 molecular sieve is a mesoporous molecular sieve with a two-dimensional pore structure and a pore size of 0.55 nanometers. It is well known that titanium silicon molecular sieve has Lewis acidity and has an irreplaceable catalytic effect in many reaction systems.

[0098] Fig.17 , Fig.18 This is the XRD diffraction pattern and scanning electron microscope (SEM) photo of commercial TS-1 molecular sieve. It can be seen that its XRD diffraction pattern is consistent with the standard card, indicating that it is a pure phase TS-1 molecular sieve. The SEM photo shows that the TS-1 molecular sieve is a nearly spherical crystal with a crystal diameter of about 300 nanometers. The BET specific surface area of ​​the TS-1 molecular sieve is 335 m 2 Elemental analysis showed that the silicon / titanium atomic ratio of the TS-1 molecular sieve sample was 94.

[0099] Table 15.1 Removal rate of TS-1 molecular sieve abrasive on silicon surface-silicon carbide wafer

[0100] As shown in Table 15.1, the removal rate of the polishing liquid for silicon surface-silicon carbide wafer is 0.64 μm / h (pH=4) and 0.51 μm / h (pH=8.5), which is significantly higher than silica sol abrasive, slightly higher than nano Na-Y molecular sieve abrasive, but lower than α-Al2O3 abrasive.

[0101] Example 16: Sn-Beta as abrasive In Example 16, the α-Al2O3 abrasive in Example 1 is replaced with Sn-Beta molecular sieve of the same mass to polish the silicon carbide wafer.

[0102] The only difference from 1.1 of Example 1 is that the 20.0 g of α-Al2O3 abrasive in step 1 is replaced by 20.0 g of Sn-Beta molecular sieve, and the rest is the same as Example 1. The Sn-Beta molecular sieve used here is a commercial Sn-Beta molecular sieve with a particle size of nanometers and no more than 300 nanometers. The crystal structure of the Sn-Beta molecular sieve is the same as the traditional Beta molecular sieve, which is a BEA structure. It is a hydrophobic tin-silicon type molecular sieve (does not contain aluminum) and a macroporous molecular sieve with a three-dimensional pore structure, with a pore size of 0.55~0.7 nanometers. As is known to all, tin-silicon molecular sieve has Lewis acidity and has an irreplaceable catalytic effect in many reaction systems.

[0103] Fig.19 , Fig. 20 This is the XRD diffraction pattern and scanning electron microscope (SEM) photo of commercial Sn-Beta molecular sieve. It can be seen that its XRD diffraction pattern is consistent with the standard card, indicating that it is a pure phase Sn-Beta molecular sieve. The SEM photo shows that the Sn-Beta molecular sieve is a nearly spherical crystal with a crystal diameter of no more than 300 nanometers, and a large number of crystals have a diameter of less than 100 nanometers. Elemental analysis shows that the silicon / tin atomic ratio of the Sn-Beta molecular sieve sample is 78.

[0104] Table 16.1 Removal rate of Sn-Beta molecular sieve abrasive on silicon surface-silicon carbide wafer

[0105] As shown in Table 16.1, the removal rate of the polishing liquid for silicon surface-silicon carbide wafer is 0.66 μm / h (pH=4) and 0.52 μm / h (pH=8.5), which is significantly higher than silica sol abrasive and nano Na-Y molecular sieve abrasive, and even higher than traditional α-Al2O3 hard abrasive. In view of the small particle size and lower hardness of Sn-Beta molecular sieve, it is more suitable as abrasive for fine polishing liquid.

[0106] Example 17: Using ZSM-23 molecular sieve with 1-dimensional channels as abrasive Example 17: The α-Al2O3 abrasive in Example 1 is replaced by nano ZSM-23 molecular sieve of the same mass, that is, the nano ZSM-23 molecular sieve is used as the abrasive to polish the silicon carbide wafer. The ZSM-23 molecular sieve here is a rod-shaped crystal with a diameter of about 50 nanometers and a length of about 300-400 nanometers.

[0107] The only difference from 1.1 of Example 1 is that the 20.0 g of α-Al2O3 abrasive in step 1 is replaced by 20.0 g of nano ZSM-23 molecular sieve, and the rest is the same as Example 1. The nano ZSM-23 molecular sieve used here is a commercially available nano ZSM-23 molecular sieve, and the crystal morphology is rod-shaped crystals with a diameter of about 50 nanometers, a length of about 300-400 nanometers, and a regularity ratio of about 80. This ZSM-23 sample was provided by Jiangsu Xianfeng Nanomaterials Co., Ltd., model XFF-18 (XRD and SEM are shown in Figures 1 and 2, respectively). Fig.21 and 22 , provided by the manufacturer). The BET specific surface area of ​​the sample is 152 m2 / g.

[0108] ZSM-23 is a microporous high-silicon molecular sieve with an MTT crystal structure. It has a one-dimensional pore composed of ten-membered rings and a pore size of 0.52*0.45nm.

[0109] Fig.21 and Fig. 22 They are the XRD diffraction pattern and scanning electron microscope (SEM) photo of ZSM-23 molecular sieve. It can be seen that its XRD diffraction pattern is consistent with the standard card, indicating that it is a pure phase ZSM-23 molecular sieve. The SEM photo shows that the ZSM-23 molecular sieve has a uniform rod-shaped particle size, with a diameter of about 50 nanometers and a length of 300~400 nanometers. The BET specific surface area of ​​the molecular sieve is 152 m 2 / g. The removal rate of the polishing liquid on the silicon surface-silicon carbide wafer is 0.23 μm / h (pH=4) and 0.29 μm / h (pH=8.5), which is slightly higher than the silica sol abrasive with the same concentration (see Table 17.1).

[0110] It can be seen that the removal rate of ZSM-23 molecular sieve is comparable to that of silica sol, and significantly lower than that of molecular sieves with 2-dimensional and 3-dimensional pore structures such as Beta, Y, and EMT, with no obvious advantages. We believe that the 1-dimensional pores of ZSM-23 are the cause of its low removal rate. Compared with molecular sieves with 2-dimensional and 3-dimensional pore structures, the 1-dimensional pore structure is not conducive to the mass transfer and diffusion of raw materials, intermediates and products, and is not conducive to mass transfer and reaction. In addition, molecular sieves with 1-dimensional pores usually have a lower BET specific surface area and fewer corresponding active sites, which is not conducive to the adsorption and reaction of raw materials and intermediates, and affects the reaction rate.

[0111] Table 17.1 Removal rate of ZSM-23 molecular sieve abrasive on silicon surface-silicon carbide wafer

[0112] It can be seen from Examples 1 to 17 that not all types of molecular sieves can achieve good results when used as abrasives to prepare chemical mechanical polishing liquids. Molecular sieves with 2D and 3D channel structures have higher removal rates than 1D channel molecular sieves. The acidity (hydrogen ion exchange) and alkalinity (alkali metal ion exchange) of molecular sieves promote polishing. Transition metal ion exchange can catalyze the reaction process and increase the removal rate. And the pH value of the polishing liquid has significantly different effects on different molecular sieves.

[0113] In general, when micron-sized Na-Y molecular sieve (particle size of 600~800 nanometers), submicron-sized HY molecular sieve (particle size of 600~800 nanometers), nano-Mn-Y molecular sieve, nano-Cu-Beta molecular sieve, and Sn-Beta molecular sieve are added to the polishing liquid with a pH value of 4.0 at a concentration of 2wt%, they can obtain a removal rate higher than other molecular sieves, and higher than or equivalent to the removal rate of commercial α-Al2O3. However, compared with commercial α-Al2O3, the hardness of the molecular sieve material is lower (the hardness is only 3~5, which is much lower than the commonly used α-Al2O3 abrasives), and it will not scratch the wafer. The polished wafer has a higher surface flatness.

[0114] When nano-EMT molecular sieve, nano-Cu-EMT molecular sieve, nano-Cu-Beta molecular sieve, and Sn-Beta molecular sieve are added to the polishing liquid with a pH value of 8.5 at a concentration of 2wt%, they can obtain a removal rate higher than other molecular sieves, and higher than or equivalent to the removal rate of commercial α-Al2O3. However, compared with commercial α-Al2O3, the hardness of the molecular sieve material is lower (the hardness is only 3~5, which is much lower than the commonly used α-Al2O3 abrasives), and it will not scratch the wafer. The polished wafer has a higher surface flatness.

[0115] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to specific details.

Claims

1. A chemical mechanical polishing liquid containing molecular sieve particles, characterized in that: It is prepared by the following steps: S1, mixing molecular sieve particles with deionized water to obtain liquid A; S2, dissolving the oxidant in deionized water to obtain liquid B; S3, mixing liquid A and liquid B, adding an additive, stirring evenly, and obtaining a polishing liquid; The molecular sieve is a molecular sieve material having a two-dimensional or three-dimensional pore structure among the molecular sieves defined by the International Molecular Sieve Association, including at least one of the following types of molecular sieves: type A, type X, type Y, mordenite, CHA, Beta, MFI, EMT, MCM-22, AlPO-18, SAPO-34; Alternatively, the molecular sieve is a hydrogen-type molecule or an alkali metal / alkaline earth metal ion-exchanged molecular sieve or a transition metal ion-exchanged molecular sieve or a rare earth metal ion-exchanged molecular sieve; Alternatively, the molecular sieve is at least one of a molecular sieve exchanged with sodium ions, potassium ions, calcium ions, magnesium ions, copper ions, nickel ions, cobalt ions, iron ions, manganese ions or zinc ions; Alternatively, the molecular sieve is a molecular sieve doped with framework elements, including at least one of TS-1, TS-2, Ti-Beta, Ti-Mor, Ti-MWW, Sn-Beta, Sn-MFI, Sn-MOR, Sn-MWW, and Sn-USY molecular sieves.

2. The chemical mechanical polishing liquid containing molecular sieve particles according to claim 1, characterized in that: The particle size of the molecular sieve particles is between 5 nanometers and 20 micrometers, and the BET specific surface area exceeds 100 square meters / gram.

3. The chemical mechanical polishing liquid containing molecular sieve particles according to claim 1, characterized in that: The oxidant is selected from one or more of permanganate, manganate, hydrogen peroxide, persulfate, cerium ammonium nitrate, periodic acid, chlorate, hypochlorite, bromate, ferrate, dichromate, and chromate; The additives include one or more of abrasive particles, dispersants, and pH regulators; The abrasive particles are selected from one or more of aluminum oxide, silicon dioxide, zirconium dioxide, titanium dioxide, silicon carbide, boron carbide, silicon nitride and diamond; The pH adjuster is selected from one or more of phosphoric acid, hydrogen phosphate, nitric acid, sulfuric acid, potassium hydroxide, sodium hydroxide, ammonia water, triethanolamine, oxalic acid, and amino acids.

4. The chemical mechanical polishing liquid containing molecular sieve particles according to claim 1, characterized in that: The concentration of the molecular sieve in the polishing liquid is 0.1-50wt%, the pH of the polishing liquid is 1.0-14.0, and the molar concentration of the oxidant is 0.01-5.0mol / L.

5. The chemical mechanical polishing liquid containing molecular sieve particles according to claim 4, characterized in that: The concentration of the molecular sieve in the polishing liquid is 2wt%, the pH of the polishing liquid is 4.0, the molecular sieve is any one of submicron Na-Y molecular sieve, submicron HY molecular sieve, nano Mn-Y molecular sieve, nano Cu-Beta molecular sieve, Sn-Beta molecular sieve, and the particle size of the submicron Na-Y molecular sieve and the submicron HY molecular sieve is 600~800 nanometers.

6. The chemical mechanical polishing liquid containing molecular sieve particles according to claim 4, characterized in that: The concentration of the molecular sieve in the polishing liquid is 2wt%, the pH value of the polishing liquid is 8.5, and the molecular sieve is any one of nano EMT molecular sieve, nano Cu-EMT molecular sieve, nano Cu-Beta molecular sieve, and Sn-Beta molecular sieve.

Citation Information

Patent Citations

  • Chemical mechanical polishing composition for copper comprising zeolite

    CN101541913A

  • Chemical mechanical polishing composition containing polysilicon polish finisher

    CN102131885A

  • Polishing slurry for chemical mechanical polishing

    CN103436231A

  • Improved polish composition

    EP0107354A1

  • Polishing agent and polishing sheet

    JP2003105327A